Narrative and violence: the Brazilian Autumn coverage on Twitter - Raquel Recuero; Marco Toledo Bastos; Gabriela Zago (Matrizes, 2014)
This paper analyses the media coverage of the Brazilian protests that happened in June 2013. We monitored 2,852 tweets from ten news organizations and newspapers that were covering the events on Twitter and, based on content analysis, we compared and identified messages focusing on violence aspects of the manifestations. We also compared this discourse to official data from 268 protests that occurred during the same timeframe, regarding deaths, injuries and arrests. Our results indicate that news coverage on Twitter diverged from official sources, amplifying the violence discourse by focusing tweets’ contents on this topic.